Analysis of the spatial structure of the trees of a tropical dry forest through point process theory (2019)
A marked point pattern of a tropical dry forest, obtained from the locations of each plant in a one-hectare plot located in the national natural park El Tuparro in the Colombian Orinoquia was analysed. We used two qualitative marks species and size, and a quantitative mark diameter at breast height-dbh. The objective of the present study was to evaluated at an ecological community level, the spatial distribution of the plants with the marked point pattern, to understand the processes of facilitation and competition that have an influence on the generated point pattern. We propose a methodology based on different tools of point process theory: first we estimated the intensities using a kernel and the incorporation of a covariate (distance to rocks); then we used different second order tools to analyse the inter and intra dependences of each of the marks; and finally we used three classification methods to group the species by their spatial behaviour, one based on dispersal indices and the other two on second order functions. The results show an influence of the rocky soil over the spatial distribution of the plants inside the study area; the second order functions indicate an inhibition pattern for all of the species, and for some a cluster pattern at close distances was identify; the size of the plants also influence the spatial distribution, large and medium trees tend to created small clusters pattern with a radius of 1.3 meters, while small plants aggregated more around big plants than around medium plants; the three types of information used for the classification analysis show similarities in the groups of species form, however, the second order functions displays better classification results.